Desert flower - Hormann, Sherry; Kebede, Liya, 1978-; Hawkins, Sally; Parkinson, Craig; Dirie, Waris (New York, NY : Virgil Films, 2011)
A woman escapes from an arranged marriage at the age of thirteen and embarks upon a two-hundred-mile journey across the desert of Somalia in an adventure that eventually leads her into a modeling career.
Based on the novel by Waris Dirie.
Originally released as a motion picture in 2009.
Features: extended interviews with Liya Kebede ; theatrical trailer.
Liya Kebede, Sally Hawkins, Craig Parkinson.
MPAA rating: R.
DVD, Dolby digital stereo.
Keywords: Dirie, Waris -- Drama; Dirie, Waris -- Film adaptations; Women social reformers -- Somalia -- Drama; Models (Persons) -- Somalia -- Drama; Fiction films; Based on the book; Feature films; Biographical films